The contributions of rural livelihoods towards household poverty alleviation in Mogodi Village, Limpopo Province - Thobakgale, Mampopelele Piet (My University, 2014)
The inability of numerous strategies that are implemented globally with the intention of alleviating poverty that households are experiencing has pushed poor people to venture into various livelihoods to generate income and produce food. Rural livelihoods are globally accepted by poor people as a reliable strategy to alleviate poverty by generating income that provide them with more purchasing power and by producing nutritious food that improve their well-being. However, there are households that practice livelihoods, yet they are poor, being unable to produce more sufficient food and income. This study, therefore, argues that rural livelihoods contribute to households’ poverty differently and their success in alleviating poverty is determined by their outputs and context(geographical, economical, and environmental) that they are operating in. The study investigated the contributions of livelihoods towards households’ poverty in rural areas using various methodologies. Systematic sampling was applied to select 100 households that are practicing livelihoods, normative research as applied; both qualitative and quantitative research approaches were used to conduct the study. Additionally, qualitative and quantitative research approaches were also used to analyze textual, observations and literature that were collected. The study concluded that rural livelihoods are very significant for the majority of poor people globally, including households in Mogodi Village as they have the potential to alleviate poverty through generation of income and food production.
Thesis (M.Dev. ) -- University of Limpopo, 2014
Keywords: Poverty; Social status; Quality of life; Rural poor -- Economic conditions; Rural development projects -- South Africa -- Limpopo; Poverty -- South Africa -- Limpopo